Modeling one typical digital differential relay in the MATLAB - Ali Saket, Mohammad; Moghaddami, Masood; Alishahi, Ehsan (Видавництво Львівської політехніки, 2011)
Differential relays are widely used in the Power networks as a protection for power transformers, bus bars and generators. This paper aims tomodel one typical differential relay in the SIMULINK environmental. This model has been simulated in the MATLAB program and the results confirmed truth of the proposed model. Also, thismodel is used to build differential relay block inMATLAB software. SinceMATLABsoftware does not have a differential relay block, this block can be used in other power system's simulations as a differential relay.
Моделювання одного типового цифрового диференціального реле в MATLAB
Keywords: Digital differential relay; modeling; MATLAB